Design of a high speed and low latency crypto-processor ASIC - Ali, Md. Liakot; Roy, Niranjan; Faisal, Fazle Elahi; Mohd Ali, Mohd Alauddin; Aris, Ishak (IEEE, 2008)
This paper presents the design of an ultra high speed crypto-processor for next generation IT security. It addresses the next generation IT security requirements: the resistance against all attacks and high speed with low latency. The proposed processor is capable of generating cryptographically secured information at a rate of multi-ten Gbps. The performance of the processor is compared with that of other researchers which proves it's superiority over them.